2012
DOI: 10.1167/iovs.12-10660
|View full text |Cite
|
Sign up to set email alerts
|

TheUCP1−3826A/G Polymorphism Is Associated with Diabetic Retinopathy and IncreasedUCP1andMnSOD2Gene Expression in Human Retina

Abstract: This study suggests that the -3826A/G polymorphism is associated with DR in type 1 DM patients. This is the first report demonstrating UCP1 gene expression in human retinas and indicates that the -3826A/G polymorphism influences its expression. In addition, the -3826G allele was associated with increased MnSOD2 expression; thus, suggesting that this allele could be a marker of oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…27 A polymorphism in the -3826A/G allele of uncoupling protein (UCP)-1 has also been reported to diminish UCP-1's protective effects against ROS, thus increasing oxidative stress in diabetic patients. 28 In addition, 866G/A, Ala55Val, and 45-bp insertion/deletion polymorphisms in UCP-2 genes have been associated with the promotion of DR by also decreasing UCP-2's protective effects against ROS. 29 …”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…27 A polymorphism in the -3826A/G allele of uncoupling protein (UCP)-1 has also been reported to diminish UCP-1's protective effects against ROS, thus increasing oxidative stress in diabetic patients. 28 In addition, 866G/A, Ala55Val, and 45-bp insertion/deletion polymorphisms in UCP-2 genes have been associated with the promotion of DR by also decreasing UCP-2's protective effects against ROS. 29 …”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Recent studies have shown an association between UCP1 -3826A/G polymorphism and retinopathy in type I diabetic patients [64]. However, the exact role of UCPs in mitochondrial homeostasis in the development of diabetic retinopathy remains to be explored.…”
Section: Mitochondrial Damagementioning
confidence: 99%
“…Slides were incubated with primary antibody and then with a biotinylated secondary antibody, streptavidinYhorseradish peroxidase conjugate (LSAB; Dako Cytomation, Inc., Carpinteria, CA), and diaminobenzidine tetrahydrochloride (kit DAB; Dako Cytomation, Inc.). Quantifications of TNF, IL-6, IL-1A, IFN-F, and TF proteins were performed by digital image analyses using Image Pro Plus software, version 4.5 (Media Cybernetics, Bethesda, MD) (49). Images were visualized through a Zeiss microscope (model AXIOSKOP-40; Carl Zeiss, Oberkochen, Germany) and captured using the Cool Snap-Pro CS (Media Cybernetics) camera in a blinded fashion.…”
Section: Brain-dead Patients and Controlsmentioning
confidence: 99%